PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN BUDAYA RELIGIUS PESERTA DIDIK - Ohan supriatna; M. Yusron Maulana El Yunusi; Eli Masnawati (TARBIYAH DARUSSALAM: JURNAL ILMIAH KEPENDIDIKAN DAN KEAGAMAAN, 2026)
Abstract This article aims to describe the role of Islamic Religious Education Teachers (GPAI) in enhancing students' religious culture. This research is a qualitative study using data collection techniques through observation, interviews, and documentation. The results show that GPAI plays a strategic role as educators, role models, spiritual guides, motivators, and guardians of religious habits. Religious culture is realized through ubudiyah yaumiyah programs such as dhuha prayer and congregational dhuhur prayer, tadarus (Islamic study), istighosah (Islamic study), and the School of Quranic Recitation Movement. This success is supported by school policies and parental support, while obstacles include the suboptimal involvement of non-PAI teachers and the lack of continuity in habituation at home.  Keywords: Islamic Education Teacher; Religious Culture; Students   Abstrak Artikel ini bertujuan mendeskripsikan peran Guru Pendidikan Agama Islam (GPAI) dalam meningkatkan budaya religius peserta didik. Penelitian ini merupakan penelitian kualitatif dengan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa GPAI berperan strategis sebagai pendidik, teladan, pembimbing spiritual, motivator, dan pengawal pembiasaan ibadah. Budaya religius diwujudkan melalui program ubudiyah yaumiyah seperti sholat dhuha, sholat dhuhur berjamaah, tadarus, istighosah, dan Gerakan Sekolah Mengaji. Keberhasilan tersebut didukung oleh kebijakan sekolah dan dukungan orang tua, sementara hambatannya meliputi keterlibatan guru non-PAI yang belum optimal dan kurangnya kesinambungan pembiasaan di rumah.   Kata kunci: Guru PAI; Budaya Religius; Peserta Didik